Understanding severely affected chronic fatigue syndrome (CFS): the gravity of the situation. (4th July 2017) - Strassheim, Victoria; Ballantine, Robert; Hackett, Katie L.; Frith, James; Newton, Julia L.
Abstract : Objective: To describe how the effects of gravity may adversely affect the neuro-cardiovascular physiology of individuals with severe Chronic Fatigue Syndrome (CFS). Design: A narrative review of the literature relating to microgravity, orthostatic intolerance and severe CFS. Emphasis is placed on the clinical significance and implications for the management of patients with severe CFS, with suggestions for future rehabilitation and physical interventions. Results: Physiological functions in humans have evolved to counter the effects of gravity, in particular the neuro-cardiovascular system. Reducing exposure to gravity will result in deconditioning of these systems. Many of the symptoms experienced by astronauts returning to Earth are shared by those with severe CFS. Prolonged periods in the supine position create an environment similar to microgravity – the mechanism through which we propose orthostatic intolerance develops in CFS. However, there are also some physiological changes present in CFS which may exacerbate these changes. Studies have shown that some CFS individuals have hypovolaemia unrelated to deconditioning. This pre-existing hypovolaemia may make the neuro-cardiovascular system more vulnerable to the effects of bed rest in those individuals with CFS. Conclusion: Severely affected CFS individuals may be more susceptible to a specific type of deconditioning, related to reduced exposure to gravity, due to pre-existing vulnerabilities in their cardiovascular and autonomic nervous systems. Rehabilitation which targets the neuro-cardiovascular system and its response to upright posture may improve function and symptoms of severely affected CFS individuals.